Analisis Keselamatan dan Kesehatan untuk Pekerja di Depot Supply Point (DSP) PT. Pertamina Lubricants Semarang - Dany, Muhammad Avril Firmansyah; Rahayu, Puspita Puji (Universitas Pahlawan Tuanku Tambusai, 2025)
In the warehousing sector, management is very focused on time efficiency, accuracy in work, and productive workers. The use of tools in work is certainly needed by workers to help complete the work. Depot Supply Point (DSP) PT Pertamina Lubricants Semarang is one of the oil warehousing locations managed by PT Pertamina Lubricants. The use of safety equipment and vigilance in work is very necessary to avoid work accidents. The purpose of this study was to determine the importance of implementing Occupational Safety and Health (K3) and prevention to minimize accidents in work. This study is included in descriptive research that presents data using a descriptive statistical approach. The results of the findings in the field showed that several workers did not understand the importance of safety in work due to less comprehensive K3 training and the use of PPE that was not optimal because the workers only partially used safety equipment.